Respondent behaviour in panel studies: a case study for income-nonresponse by means of the British Household Panel Study (BHPS) - Jorg-Peter Schrapler (University of Essex, Institute for Social and Economic Research (ISER), 2003)
Many validation studies deal with item-nonresponse and measurement error in earning data. In this paper we explore motives of respondents for the failure to reveal earnings using the British Household Panel (BHPS). BHPS collects socio-economic information of private households in Great Britain. We explain the evolution of income-nonresponse in the BHPS and demonstrate the importance of a discrimination between refusing the income-statement or dont know.
Keywords: 330